Ekonomi Digital sebagai Penggerak Pertumbuhan Ekonomi di Indonesia - Wahyu Muh Syata (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The development of information and communication technology has driven the emergence of the digital economy as a new driver of economic growth, including in Indonesia. This study aims to analyze the role of the digital economy as a driver of national economic growth. The method used is a literature study (library research) by reviewing various sources in the form of relevant scientific journals, books, and official reports. Data analysis techniques were conducted using descriptive qualitative techniques through the process of collecting, categorizing, and interpreting the results of previous research. The results of the study indicate that the digital economy has a significant contribution to improving operational efficiency, expanding market reach, and encouraging business innovation. The use of digital technologies such as e-commerce and fintech has been proven to increase productivity and income, particularly in the Micro, Small, and Medium Enterprises (MSMEs) sector. Furthermore, the digital economy also plays a role in maintaining the stability of economic activity during times of crisis and encouraging economic inclusion by increasing access to a wider market. The development of the digital economy still faces various challenges, such as limited digital infrastructure, low technological literacy, and disparities in access between regions. Therefore, government policy support, equitable digital infrastructure development, and improving the quality of human resources are needed to optimize the potential of the digital economy. Thus, the digital economy can become a key pillar in driving inclusive and sustainable economic growth in Indonesia.